Pelatihan Worship Leader, Singer dan Multi Media Di GPdI Imanuel Kagungan Rahayu - Nova Ritonga; Saedo Marbun (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
Worship is an important part of the Christian faith journey. In worship,there are praise and worship which is very decisive in the success ofworship. To realize successful worship, it takes people who are capableof leading worship such as worship leaders, and singers and the presenceof adequate multimedia support such as easy worship. However, manychurches do not yet have qualified ministers for these tasks, includingGPdI Imanuel Kagungan Rahayu. This public service aims to facilitateand provide training to God's ministers in the church to improve thequality of their services. This Public service is done by the trainingmethod. The participants were very enthusiastic during the training andfollowed the activity until the end. Participants can understand thematerial provided and can practice it during practice sessions. After thepublic service is done, worship leaders, singers, and multi-mediaoperators can apply the material that has been received in churchservices with full responsibility